A Cohort Study of Relations Among Caregiver–Infant Co-Occupation and Reciprocity. (October 2020) - Aubuchon-Endsley, Nicki L.; Gee, Bryan M.; Devine, Nancy; Ramsdell-Hudock, Heather L.; Swann-Thomsen, Hillary; Brumley, Michele R.
Co-occupation is the mutual engagement of two people in a shared occupation. Recent research has investigated co-occupational activities during sensitive periods to inform clinical practice. However, there remains a dearth of applied research to bridge gaps between research and practice within salient co-occupational relationships between caregivers and infants. The study applied co-occupational constructs of physicality, emotionality, and intentionality within caregiver–infant dyads across infancy. These constructs were examined in relation to caregiver–infant reciprocity in other domains (i.e., language, motor, and affective) to determine the overlapping features of reciprocal co-occupation with established aspects of reciprocity. Results suggest that as infants transitioned into toddlerhood and became more mobile and intentional in behavior, there were observable changes in caregiver–infant reciprocity. Caregiver utterances, affect, touch, and co-occupation were significantly related within and across time, highlighting the need for more studies to disentangle these relations in reference to infant development.